A Friend in Need or a Business Indeed?: Disabled Bodies and Fraternalism in Victorian Ontario - Galer, Dustin (Labour (Halifax), 2010)
During the period of early capitalism in Ontario, disabled workers were forced to find ways to survive following an injury. Affordable insurance offered by fraternal societies provided limited protection for many working-class families but was not a reliable source of financial support for injured and disabled workers. Even when insurance disability benefits were a factor, many injured workers soon found themselves in a position of financial hardship. Fraternal insurance reflected many of the same barriers facing disabled workers and as a result, represents a microcosm of wider social and institutional treatment of individuals with disabilities during this period. Durant la période du début du capitalisme en Ontario, les travailleurs handicapés étaient obligés de trouver des moyens de survivre par suite d'une blessure. L'assurance abordable offerte par les sociétés fraternelles donnait de la protection limitée pour de nombreuses familles de classe ouvrière mais n'était pas une source fiable d'appui financier pour les travailleurs blessés ou handicapés. Même si les prestations d'assurance invalidité étaient en jeu, de nombreux travailleurs blessés se sont vite trouvés dans une position de difficulté financière. L'assurance fraternelle a révélé les mêmes barrières nombreuses faisant face aux travailleurs handicapés et en conséquence, représente un microcosme du traitement social et institutionnel plus large des personnes frappées d'incapacité pendant cette période.